Longitudinal in vivo MRI in a Huntington’s disease mouse model: global atrophy in the absence of white matter microstructural damage - Steventon, Jessica J.; Trueman, Rebecca C.; Ma, Da; Yhnell, Emma; Bayram-Weston, Zubeyde; Modat, Marc; Cardoso, Jorge; Ourselin, Sebastian; Lythgoe, Mark; Stewart, Andrew J.; Rosser, Anne E.; Jones, Derek K. (Nature Publishing Group, 2016)
Huntington’s disease (HD) is a genetically-determined neurodegenerative disease. Characterising neuropathology in mouse models of HD is commonly restricted to cross-sectional ex vivo analyses, beset by tissue fixation issues. In vivo longitudinal magnetic resonance imaging (MRI) allows for disease progression to be probed non-invasively. In the HdhQ150 mouse model of HD, in vivo MRI was employed at two time points, before and after the onset of motor signs, to assess brain macrostructure and white matter microstructure. Ex vivo MRI, immunohistochemistry, transmission electron microscopy and behavioural testing were also conducted. Global brain atrophy was found in HdhQ150 mice at both time points, with no neuropathological progression across time and an elective sparing of the cerebellum. In contrast, no white matter abnormalities were detected from the MRI images or electron microscopy images alike. The relationship between motor function and MR-based structural measurements was different for the HdhQ150 and wild-type mice, although there was no relationship between motor deficits and histopathology. Widespread neuropathology prior to symptom onset is consistent with patient studies, whereas the absence of white matter abnormalities conflicts with patient data. The myriad reasons for this inconsistency require further attention to improve the translatability from mouse models of disease.